The Effect of Low-Density Polyethylene Addition and Temperature on Creep-recovery Behavior of Hot Mix Asphalt - Mahammed Mazouz; M. Merbouh (Civil Engineering Journal, 2019)
Industrial and domestic plastic waste is second harmful products to the environment. Considering the technological development and the current way of life, this non-biodegradable waste and its enormous quantities threaten the balance of the ecosystem and human health. The present study was an attempt to investigate the effect of Low-density polyethylene “LDPE” plastic waste, used us asphalt additive, on creep-recovery behavior of Hot Mix Asphalt (HMA). This technique is a contribution to the improvement of the quality and cost of HMA, for alternate materials. In this experimental study, two mixes of asphalts were prepared, basic and modified asphalts, and tested in four points bending test at two different temperatures, medium (20°C) and high temperature (50°C). The use of 5 % of LDPE gave a better thermo-mechanical performance. As well as, a decrease in total deformation by 51 % and 13 % at 20°C and 50°C respectively. A clear improvement of the resistance to the creep permanent deformation, rigidity and lasted in life. This modification serves a powerful, economic and environmental solution for road construction of hot Saharan areas at medium and high temperature of service.